Severe preeclampsia leads to higher prevalence of mortality and morbidity affecting maternal outcomes in single tertiary hospital - Khonsa’ Tsabitah; Budi Wicaksono; Samsriyaningsih Handayani (Universitas Airlangga, 2020)
Objective: The purpose of this study was to determine the maternal outcomes of severe preeclampsia at RSUD Dr. Soetomo Surabaya in January 2013-December 2014.Materials and Methods: This research was a descriptive study with cross-sectional design to observe maternal characteristics and maternal outcomesof severe preeclampsia. Data were retrieved from medical records of severe preeclampsia patients admitted to Obstetric Ward of Dr Soetomo Hospital, from January 2013 to December 2014. This study used total sampling for collecting its data. These data were proccessed descriptively and presented in graphic, tables, and short description.Results: From January 2013 to December 2014 there were 386 (44.2%) cases of severe preeclampsia that were included in this study from a total of 874 cases available. The maternal outcomes of severe preeclampsia consisted of 42 cases (10.9%) of HELLP syndrome, 36 cases (9.3%) of pulmonary edema, 225 cases (58.3%) of sectio caesarea, 7 cases(1.8%) of antepartum bleeding with 5 cases (1.3%) of placenta previa and 2 cases (0.5%) of solutio placenta, 2 cases (0.5%) of postpartum bleeding, 8 cases (2.1%) of eclampsia, 31 cases (8%) of impending eclampsia, 5 cases (1.3%) of acute kidney injury, and 2 cases (0.5%) of maternal death.Conclusion: In conclusion, this study shows that severe pre-eclampsia patients have high prevalence of mortality and morbidities that affects maternal outcomes. It also reccommends that all patients with severe preeclampsia need to receive intensive maternal and fetal care. It is necessary to do careful complication examination, prevention of seizures using magnesium sulfate, and continous fetal and maternal monitoring.